ADAPTASI DELAPAN NOMOR HARAPAN KUNYIT (Curcuma domestica Vahl.) TOLERAN NAUNGAN - Sitti Fatimah Syahid; Cheppy Syukur; Nathalini Nova Kristina; Joko Pitono (Pusat Penelitian dan Pengembangan Perkebunan, 2012)
Turmeric cultivation by farmer is mainly conducted under shading, so it needed turmeric superior seeds especially for shading cultivation. The aim of the research was to analiysis the adaptability based on yield and quality stability of turmeric promising lines under shading on three different agroecology Adaptation test for releasing the superior variety of crops was conducted at three locations of turmeric central production in Bringin 464 m asl, Nogosari, 425 m asl, and Simo 484 m asl. Tested was done in 2008 until 2010 under famer’s teak plantations. Eight promising lines of turmeric out of 70 accessions selected under artificial shading season in year of 2007/2008 at Cicurug, Sukabumi (West Java) and one local number were used as materials to be tested. The experiment was arranged in Randomized Block Design with three replications. Each block consisted of 48 plants. The observed parameters were growth component, yield, and curcumin content. Combined varian analysis result showed that there was no interaction effect between genotype and environment on the yield and curcumin content. However, all of the tested genotypes were signicifantly differed for their curcumin content. Turmeric promising line Cudo 04, with rhizome yield 0f 7.4 ton ha-1, had the highest curcumin (7.05%) and essential oil content (4.77%), and tolerant to the leaf spot disease. Therefore, this line is recommended to be released as a superior variety tolerant to shading. Based on its curcumin content, this line was also found as a superior one to be developed by herbal medicine industry.